A CLINICAL CASE OF HYDROALLONTOIS IN A PLEURIPAROUS NON-DESCRIPTIVE BUFFALO. - BALAMURUGAN, B; Reddy, YV PRIDHVIDHAR; JYOTHI, K (The Indian Journal of Animal Reproduction, 2020)
A 2nd parity, non-descriptive 8th month pregnant buffalo was presented to DVCC with the history of bilateralabdominal enlargement since 7-10 days. Had treatment history of dexamethasone, oxytetracycline. Had vaginalwatery discharge since two days. Animal had anorexia and not taking water since two days. General clinical examinationrevealed dull and depressed, all the vital parameters were not within the normal range. Hence it is diagnosed ashydroallantois. Animal was stabilized with fluid therapy. On per- rectal examination revealed tough fluid filled uterus.On per-vaginal examination revealed cervix was dilated three fingers. Cervix was dilated through fanning and fathering.A dead male calf was relieved through mutational operations. Fetal fluids were drained slowly. After draining the fluidsanimal is administered with fluids and advised for antibiotic therapy for 3 days. Animal had uneventful recovery.
Keywords: Hydroallontois; Buffalo; Dexamethasone; Vaginal discharge; Fetal fluids